Perkosaan Ayah pada Anak Kandung yang Masih di Bawah Umur dalam Perspektif Hukum Pidana Islam dan Hukum Pidana - Bakara, Monica Anamaloka; Sitepu, Rajin; Harahap, Mar’ie Mahfudz (Lembaga Yasin AlSys, 2023)
The main problem in this thesis is how the provisions regarding the rape of a father on a biological child who is still underage in the view of Islamic criminal law and criminal law. Rape is a form of violence by coercion in subtle or gross forms, and has a negative impact on the future of the victim, especially since the victim is still a child (underage) both socially and psychologically. This thesis aims to explain the provisions of the views of Islamic law and criminal law regarding rape of minors committed by their own biological father. This research uses a qualitative method that is descriptive analytical, with a normative juridical approach. With the research object of legislation relating to legal theories. The data collection technique used in this research is library research and this method is used to complete the data needed in writing this thesis, namely by looking at laws and books related to the subject matter to be examined. The results of this study indicate that the sanctions against the perpetrators of the crime of father rape on their biological children who are still underage and in terms of Islamic criminal law, the first opinion is that the perpetrators are sentenced to stoning, the second opinion is to give punishment to the perpetrators of ta'zir punishment, the result and type of punishment are left to ruler's decision. In terms of criminal law, the defendant is given a maximum prison sentence of 15 years and a maximum fine of five billion rupiah which is contained in article 81 of Law Number 35 of 2014 concerning Child Protection, the criminal provisions in the Elimination of Domestic Violence (PKDRT) are contained in article 47 with a minimum imprisonment of 4 years and a maximum of 15 years or a minimum fine of twelve million and a maximum fine of three hundred million rupiah. And in the application of sentencing/court decisions, namely the judge's decision itself, there is no consistency in imposing criminal sentences, namely including articles contained in the Law on the Elimination of Domestic Violence (PKDRT).